2022
DOI: 10.18865/ed.32.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Risk and Protective Factors for Cost-Related Nonadherence Among Middle East and North African (MENA ) Adults

Abstract: Objective: Cost-related nonadherence to health maintenance behaviors is common in the general population, yet we know little about these behaviors in Middle East and North African (MENA) Americans. We examined cost-related nonadherence (CRN) in the MENA community in SE Michigan to determine demographic predictors, and risk and protective factors.Design, Setting, and Participants: We used data from a cross-sectional convenience sample of MENA adults (N=398) conducted May-September 2019 to identify relevant demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Studies have reported that MENA individuals are less likely to use prescriptions, which may be due to lack of access, barriers in communication with healthcare providers due to language, or cost. 44 46 Since younger adults are more likely than older adults to report HIT use in general, there may not be a need for refilling prescriptions online among those who are healthy and do not need everyday prescriptions. Yang and colleagues found that adults ages 18–24 less likely to need prescriptions than adults ages 75 and older who were less likely to use the internet for any purpose.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that MENA individuals are less likely to use prescriptions, which may be due to lack of access, barriers in communication with healthcare providers due to language, or cost. 44 46 Since younger adults are more likely than older adults to report HIT use in general, there may not be a need for refilling prescriptions online among those who are healthy and do not need everyday prescriptions. Yang and colleagues found that adults ages 18–24 less likely to need prescriptions than adults ages 75 and older who were less likely to use the internet for any purpose.…”
Section: Discussionmentioning
confidence: 99%